Patterns of responses in metastatic NSCLC during PD-1 or PDL-1 inhibitor therapy: Comparison of RECIST 1.1, irRECIST and iRECIST criteria. (January 2018) - Tazdait, M.; Mezquita, L.; Lahmar, J.; Ferrara, R.; Bidault, F.; Ammari, S.; Balleyguier, C.; Planchard, D.; Gazzah, A.; Soria, J.C.; Marabelle, A.; Besse, B.; et al.
Abstract: Background: Immune checkpoint inhibitors are an important tool in the therapeutic strategy against metastatic non–small cell lung cancer (NSCLC); however, radiological evaluation is challenging due to the emergence of atypical patterns of responses. Several evaluation criteria have been proposed, such as the Response Evaluation Criteria in Solid Tumours (RECIST), version 1.1, immune -related RECIST (irRECIST) and iRECIST, but have not been systematically compared in a homogeneous population. Patients and methods: We conducted a monocentric retrospective analysis of consecutive advanced NSCLC patients treated with an anti–programmed cell death-1 or anti–program death-ligand 1. Response patterns and the discordance between RECIST 1.1, irRECIST and iRECIST guidelines were described, and associations of response patterns and clinical outcome were explored. Results: Overall, 160 patients treated between February 2013 and October 2016 were included. Atypical responses were observed in 20 patients (13%), including eight pseudoprogressions (PsPDs) (5%) and 12 dissociated responses (8%). Thirteen of the 20 patients demonstrated clinical benefit. Per the RECIST 1.1, 37 patients (23%) showed an objective response or stable disease, and 123 patients (77%) exhibited progression. Eighty progressive patients were assessable for irRECIST and iRECIST: 15 patients were assessed differently; however, only three (3.8%) mismatches with a theoretical impact on the therapeutic decision were identified. Patients with PsPD or dissociated response had higher overall survival than patients with true progression. Conclusion: Atypical responses (PsPD/dissociated response) occurred in 13% of NSCLC patients under immune checkpoint inhibitors. Based on survival analyses, the RECIST 1.1 evaluation underestimated the benefit of immune checkpoint inhibitors in 11% of the progressive patients. Immune-related RECIST and iRECIST identified these unconventional responses, with a 3.8% discrepancy rate. Highlights: Non–small cell lung cancer patients under immune checkpoint inhibitor may experience atypical responses. Conventional Response Evaluation Criteria in Solid Tumours (RECIST), version 1.1, are insufficient for capturing pseudoprogression. The RECIST 1.1 criteria may have underestimated the benefit of immune checkpoint inhibitors. The immune-related RECIST (irRECIST) and iRECIST are able to capture unconventional responses. The iRECIST provided highly concordant response assessment compared with irRECIST.